Outsidership, network positions and cooperation among internationalizing SMEs: An industry evolutionary perspective. Issue 3 (June 2022) - Ong, Xander; Freeman, Susan; Goxe, François; Guercini, Simone; Cooper, Brian
Abstract: Immigrant entrepreneurship, like other market entries, continues to be examined in most studies as an event, and not as a process of ongoing interactions and exchanges that would adequately address the influence on such a transition of collaborative engagements and of industry evolution in the host market. Adopting an industry evolutionary perspective, we examine the facilitating role played by cooperative strategies among immigrant-run SMEs. Using a small number of valued customer and competitor relationships, we draw from case studies to show how both immigrant and native run SMEs gain knowledge and resources through collaborative engagements to extend into new customer segments. These relationships enable them to mitigate their outsidership by adopting positions on the edges of networks that allow them to avoid competing directly against other internationalizing SMEs abroad or in their home markets. Using context to build an industry evolutionary perspective, we observe their entry into collaborative engagements with intermediaries in other business networks to build additional industry segments in the less understood maturing industry phase. This study shows how native-run Italian internationalizing SMEs accessed the resources of immigrant Chinese business networks and developed capabilities for mutual benefit. Highlights: An industry evolutionary perspective of cooperative strategies among immigrant-run SMEs. Collaborative engagements by internationalizing SMEs in other business networks build new segments as industries evolve. Outsidership is less apparent for an immigrant-run compared to a native-run SME.